Methods for glomerular quantification in dogs: a comparative study - Costa,Caio Augusto Leles (2019)
ABSTRACT: It was evaluated the different methodologies for glomerular enumeration described in the literature in a quantitative, double-blind study on the number of glomeruli present in kidney biopsy specimens obtained using a Tru-cut-type biopsy needle. Eighteen samples were taken (n=18) from various regions of canine kidneys harvested immediately after euthanasia. Sample collection was carried out using Tru-cut-type, semi-automated, 16 gauge needles. Reading and evaluation of the specimens were performed independently by four researchers by means of eye loupe inspection, light microscopy, light microscopy with a reduced condenser aperture, and dissection microscopy. Samples were also subjected to histopathological evaluation for comparison purposes. There was no inter-researcher variation for any of the tested methods. The glomerular counts obtained using light microscopy with reduced condenser aperture were similar to those reported in the histopathological evaluation (P=0.44);whereas, the other glomerular enumeration methods yielded significantly lower counts when compared to the histopathological analysis (eye loupe inspection: P<0.01; conventional light microscopy: P=0.02; dissection microscopy: P<0.01).Light microscope with lowering of the condenser lens delivers better results than conventional light microscopy and eye loupe inspection. Results obtained using dissection microscopy and eye loupe inspection did not correlate well with those provided by histopathological evaluation; consequently, these two methods should be avoided.